2018
DOI: 10.1371/journal.pone.0203315
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative diltiazem or nitroglycerin in on-pump coronary artery bypass: A systematic review and network meta-analysis

Abstract: BackgroundArterial graft spasm is a severe complication after coronary artery bypass graft (CABG). Among numerous potential antispasmodic agents, systemic application of diltiazem and nitroglycerin had been investigated most frequently over the past three decades. However, it remains inconclusive if either or both agents could improve patient outcomes by preventing graft spasm when applied perioperatively, and, if so, which one would be a better choice. The current systematic review and network meta-analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
0
7
0
1
Order By: Relevance
“…However, there has been no de nitive anatomical evidence supporting that perioperative continuous iv application of diltiazem had a direct vasodilatory effect on coronary grafts after the sternum was closed. Diltiazem became the preferred antispasmodic agent because, compared to nitroglycerine, it had more favorable perioperative outcome pro les, including lower incidences of new onset A-b and cardiac ischemia 7,9,21,22 . Noticeably, data from these RCTs also suggest that patients on diltiazem may need prolonged hemodynamic support from inotropic and/or vasoactive support, indicating that the usage of diltiazem may have potential negative perioperative and long-term outcome impacts 22 .…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been no de nitive anatomical evidence supporting that perioperative continuous iv application of diltiazem had a direct vasodilatory effect on coronary grafts after the sternum was closed. Diltiazem became the preferred antispasmodic agent because, compared to nitroglycerine, it had more favorable perioperative outcome pro les, including lower incidences of new onset A-b and cardiac ischemia 7,9,21,22 . Noticeably, data from these RCTs also suggest that patients on diltiazem may need prolonged hemodynamic support from inotropic and/or vasoactive support, indicating that the usage of diltiazem may have potential negative perioperative and long-term outcome impacts 22 .…”
Section: Discussionmentioning
confidence: 99%
“…22 A systematic review and meta-analysis from 2018 suggested that calcium channel blockers were highly effective and well tolerated for treating perioperative hypertension, and a 2018 meta-analysis suggested that continuous perioperative intravenous infusion of diltiazem had protective effects against postoperative ischemic cardiac injury and AF. 93,94 However, data from these studies are poor, and larger studies are needed.…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…Aufgrund der stetigen Veränderungen der Hämodynamik in der Akutphase der postoperativen Behandlung sollten zunächst vor allem kurzwirksame Substanzen wie Nitroglycerin oder Nitroprussid zum Einsatz kommen [72,73]. Diese medikamentöse Reduktion der linksventrikulären Nachlast nach operativer Korrektur einer vorbestehenden Mitralklappeninsuffizienz ist besonders wichtig, da eine unnötige Nachlaststeigerung den zuvor präoperativ volumenbelasteten linken Ventrikel überfordern und in ein linksventrikuläres Pumpversagen münden kann [74].…”
Section: Merkeunclassified